Nano twin crystal silver-copper alloy material and preparation method thereof

By using DC magnetron co-sputtering technology to prepare nanotwinned silver-copper alloy materials on a substrate, the problems of electromigration and thermomechanical reliability of silver materials in electronic packaging processes are solved, achieving high strength, low resistivity and high thermal conductivity, which is suitable for high-density interconnects and aerospace electronic applications.

CN121046780APending Publication Date: 2025-12-02HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511213357.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Metallic silver is prone to electromigration failure, thermomechanical reliability issues, and poor long-term service reliability during electronic packaging, which limits its application as an interconnect material.

Method used

Nanotwinned silver-copper alloy materials were prepared on a substrate using DC magnetron co-sputtering technology. By applying a DC high-voltage electric field between the silver target and the copper target, high-density nanotwin boundaries and nanocolumnar crystals were formed, thereby improving the mechanical properties and thermal stability of the material.

Benefits of technology

The prepared nanotwinned silver-copper alloy material has high strength, high resistance to electromigration, low thermal resistivity and high thermal conductivity, which significantly improves the long-term service reliability of electronic devices and is suitable for high-density interconnects and aerospace electronics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121046780A_ABST
    Figure CN121046780A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electronic packaging advanced interconnection, in particular to a nano twin crystal silver-copper alloy material and a preparation method thereof. The preparation method comprises the following steps: S1, polishing the surface of the substrate until Ra is less than or equal to 0.04 mu m; s2, carrying out ultrasonic cleaning and drying on the substrate; s3, selecting a silver target and a copper target as target materials, putting the substrate and the target materials into magnetron sputtering equipment, vacuumizing, introducing argon into a vacuum chamber, applying a direct-current high-voltage electric field, and carrying out direct-current magnetron co-sputtering deposition under the conditions that the incident angle is 0 degree, the substrate and the target materials are spaced, the temperature of the substrate is 25 DEG C, the argon flow is 30-50 sccm, the argon pressure is 6-9 mTorr and the vacuum degree of a sputtering chamber before sputtering is less than 1 * 105 Pa; the deposition time is 60 to 90 minutes. The silver-copper alloy material is good in structure uniformity, the silver-copper alloy components are adjustable, the thickness is controllable, bias voltage does not need to be applied, and the physical vapor deposition technology is adopted to be compatible with the integrated circuit manufacturing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of advanced interconnect technology in electronic packaging, and in particular to a nanotwinned silver-copper alloy material and its preparation method. Background Technology

[0002] With the rapid development of artificial intelligence, 5G communication, and the Internet of Things (IoT) technologies, electronic devices are evolving towards higher performance, smaller size, and higher reliability, posing unprecedented challenges to electronic packaging materials. Silver, with its excellent electrical and thermal conductivity and relatively low cost, stands out among many metallic materials, becoming one of the key interconnect materials in the field of electronic packaging. However, metallic silver is prone to electromigration failure, thermomechanical reliability issues, and long-term service reliability problems during service, severely limiting its application as an interconnect material. Summary of the Invention

[0003] To address the aforementioned technical problems, this invention discloses a silver-copper alloy material with a nanotwinned structure and its preparation method. The resulting material possesses excellent properties such as high strength, high resistance to electromigration, high thermal stability, low thermal resistivity, and high thermal conductivity.

[0004] This invention provides a method for preparing a nanotwinned silver-copper alloy material, comprising the following steps: S1. Polish the substrate surface to Ra≤0.04 μm; S2. Perform ultrasonic cleaning and drying on the substrate; S3. Silver and copper targets were selected. The substrate and target were placed in the magnetron sputtering equipment. After evacuation, argon gas was introduced into the vacuum chamber, and a DC high-voltage electric field was applied for DC magnetron co-sputtering deposition. The incident angle was 0°, the substrate and target were spaced apart, the substrate temperature was 25 ℃, the argon gas flow rate was 30~50 sccm, the argon gas pressure was 6~9 mTorr, and the vacuum degree of the sputtering chamber before sputtering was <1×10⁻⁶. 5 Pa, deposition time is 60~90 min.

[0005] As a further improvement of the present invention, the substrate is a copper substrate or a silicon substrate.

[0006] As a further improvement of the present invention, the thickness of the substrate is 500~1000 μm.

[0007] As a further improvement of the present invention, step S2 specifically includes: ultrasonically cleaning the polished substrate with anhydrous ethanol for 5-10 minutes, shaking off the surface moisture, and then drying it.

[0008] As a further improvement of the present invention, the purity of the silver target is 99.999%, and the purity of the copper target is 99.9995%.

[0009] As a further improvement of the present invention, the high-voltage electric field power applied to the silver target is 100~200 W, and the high-voltage electric field power applied to the copper target is 10~30 W.

[0010] As a further improvement of the present invention, the distance between the substrate and the target is 20 cm.

[0011] The present invention also provides a nanotwinned silver-copper alloy material, which is prepared by the method described above.

[0012] As a further improvement of the present invention, the nanotwin silver-copper alloy material is composed of dense columnar nanocrystals grown along the normal of the substrate with a width of less than 100 nm. The columnar nanocrystals are internally distributed with high-density nanotwin wafer layers perpendicular to the normal of the substrate. The average spacing between the nanotwin wafer layers is less than 40 nm, and the average thickness of the nanotwin wafer layers is 5~40 nm.

[0013] As a further improvement of the present invention, the thickness of the silver-copper alloy material in the nanotwin wafer layer is 2~10 μm.

[0014] The beneficial effects of this invention are: First, the silver-copper alloy material with a nanotwinned structure prepared based on the technical solution of this invention has high-density nanotwins and nanoscale columnar crystals, which significantly suppresses electromigration and thermomechanical fatigue. This material possesses low resistivity and high thermal conductivity, ensuring effective transmission and heat dissipation of high-frequency signals. Simultaneously, it exhibits high anti-electromigration performance and high thermal stability, significantly improving the long-term reliability of devices. This silver-copper alloy material with a nanotwinned structure effectively solves the problems of low mechanical properties, poor anti-electromigration performance, and poor thermal stability of traditional silver materials, making it highly suitable for interconnect layer applications in cutting-edge fields such as high-density interconnects, power modules, and aerospace electronics.

[0015] Second, the technical solution of the present invention uses DC magnetron co-sputtering technology to prepare silver-copper alloy material with nanotwin structure, which has the following advantages: (1) good uniformity of structure (2) adjustable silver-copper alloy composition (3) controllable thickness (4) no need to apply bias voltage (5) physical vapor deposition technology is compatible with integrated circuit manufacturing process (6) compared with nanotwin silver material, this material has no transition layer at the substrate interface. Attached Figure Description

[0016] Figure 1 This is a focused ion beam (FIB) image of a cross-section of a silver-copper alloy material with a nanotwin structure deposited on a copper substrate in Embodiment 1 of the present invention. Figure 2This is a focused ion beam (FIB) image of the cross-section of the silver nanomaterial deposited on a copper substrate (single-target sputtering) in Comparative Example 1 of the present invention. Figure 3 This is a focused ion beam (FIB) image of a cross-section of a silver-copper alloy material with a nanotwin structure deposited on a copper substrate in Embodiment 2 of the present invention. Figure 4 This is a focused ion beam (FIB) image of a cross-section of a silver-copper alloy material with a nanotwin structure deposited on a copper substrate in Embodiment 3 of the present invention. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail.

[0018] The present invention provides a method for preparing a nanotwinned silver-copper alloy material, comprising the following steps: Step S1: Polish the substrate surface to Ra≤0.04 μm. The substrate is a copper substrate or a silicon substrate. The substrate thickness is 500~1000 μm.

[0019] The polishing process primarily ensures the smoothness and roughness of the surface. High surface roughness and poor smoothness can lead to large-area pores at the interface between the film and the substrate, affecting the adhesion; and can also result in a smaller bonding area and lower strength during bonding.

[0020] Step S2: Perform ultrasonic cleaning and drying on the substrate. Specifically, use anhydrous ethanol to ultrasonically clean the polished substrate for 5-10 minutes, shake off the surface moisture, and then dry it.

[0021] Step S3: Target materials selected are a 99.999% pure silver target and a 99.9995% pure copper target. The substrate and targets are placed in a magnetron sputtering apparatus. After evacuation, DC magnetron co-sputtering deposition is performed. The high-voltage electric field power applied to the silver target is 100-200 W, and the high-voltage electric field power applied to the copper target is 10-30 W. The incident angle is 0° (the angle between the substrate normal and the target normal). The distance between the substrate and the target is 20 cm. The substrate temperature is 25 °C. The argon flow rate is 30-50 sccm, the argon pressure is 6-9 mTorr, and the vacuum level in the sputtering chamber before sputtering is <1×10⁻⁶. 5 Pa, deposition time is 60~90min.

[0022] Introducing a copper target into the sputtering target significantly increased the twin density and reduced the grain size compared to samples sputtered without a copper target. Thanks to the pinning effect of Cu on the twin boundaries, the nanotwin boundaries in the material exhibit higher thermal stability. These high-density, coherent nanotwin boundaries can accommodate dislocation slip and accumulation, hindering dislocation movement, and possess lower grain boundary energies. Compared to samples without a copper target, this significantly improves the material's mechanical properties, thermal stability, and resistance to electromigration.

[0023] Argon gas can provide a high-energy particle source to maintain plasma stability. After argon gas is introduced into the vacuum chamber and a DC high-voltage electric field is applied, argon atoms are ionized into argon ions (Ar). + Argon ions and electrons create a low-temperature plasma environment. This plasma is the basis of the sputtering process, providing a high-energy particle source for target bombardment. The target is bombarded, causing target atoms to sputter onto the substrate, forming a thin film. Argon ions, accelerated by an electric field, bombard the target surface at high speed, causing target atoms or molecules to detach from the surface through momentum transfer (sputtering). The sputtered target particles, in the form of neutral atoms or molecules, fly towards the substrate and deposit to form a thin film.

[0024] The present invention also provides a nanotwinned silver-copper alloy material, which is prepared by a method thereof.

[0025] The silver-copper alloy material with nanotwin structure is composed of dense, columnar nanocrystals with a width of less than 100 nm that grow along the substrate normal. Inside, there are high-density nanotwin crystalline layers that are perpendicular to the substrate normal. The average spacing of the nanotwin crystalline layers is less than 40 nm, and the average thickness of the nanotwin crystalline layers is 5~40 nm.

[0026] The thickness of the silver-copper alloy material with nanotwin structure is 2~10 μm. The surface of the nanocolumnar crystals has a high (111) preferred orientation. Ag and Cu are both FCC metals, and their (111) crystal plane has the strongest diffusion ability. Therefore, the high (111) preferred orientation is beneficial to ensure high bonding quality and reduce bonding temperature.

[0027] The silver-copper alloy material with a nanotwin structure obtained using this technical solution possesses high-density twin boundaries and high-density nanocolumnar crystals, and while ensuring low resistivity and high thermal conductivity, it also exhibits high strength, high electromigration resistance, and high thermal stability. The introduction of Cu significantly increases the density of nanotwin boundaries and reduces grain size. Simultaneously, thanks to the pinning effect of Cu on the twin boundaries, the nanotwin boundaries in the material exhibit higher thermal stability. These high-density coherent nanotwin boundaries can accommodate dislocation slip and accumulation, hindering dislocation movement, and possess low grain boundary energy. Therefore, the prepared silver-copper alloy material with a nanotwin structure exhibits excellent thermal stability and mechanical properties. Furthermore, the triangular points formed by coherent twin boundaries and grain boundaries can reduce the migration rate of atoms under electron wind forces, thereby improving the material's electromigration resistance. Therefore, this material also possesses high electromigration resistance, ensuring the reliability of devices under high current conditions. Using this nanotwinned silver-copper alloy material with a high-density nanotwinned structure as an interconnect material can yield an interconnect interface with excellent mechanical properties, high electromigration resistance, and high thermal stability. At the same time, the fabricated device has excellent long-term service reliability.

[0028] The present invention will be further described below with reference to three embodiments and one comparative example.

[0029] Example 1:

[0030] A silver-copper alloy material with a high-density nanotwinned structure is prepared on a copper substrate using DC magnetron co-sputtering technology. The method for preparing the nanotwinned silver-copper alloy material by magnetron sputtering technology in this embodiment includes the following steps: S1. Ultrasonic cleaning of the mechanically polished polycrystalline copper substrate (Ra≤0.04 μm) with anhydrous ethanol for 5~10 min; then spin dry the surface moisture and dry for later use. S2. Place the polished and cleaned polycrystalline copper substrate, 99.999% silver target, and 99.9995% copper target into the magnetron sputtering stage, and adjust the distance between the substrate and the target to 20 cm.

[0031] S3. After vacuuming, set the sputtering deposition process parameters as follows: silver target power 100 W, copper target power 30 W, incident angle adjusted to 0°, substrate temperature: 25℃, argon flow rate 50 sccm, argon pressure 9 mTorr, sputtering chamber vacuum degree before sputtering: 1×10 5 Pa, followed by DC magnetron co-sputtering deposition on the substrate.

[0032] S4. Keep step S3 for 60 min to obtain a silver-copper alloy material with a high-density nanotwin structure and a thickness of about 2 μm.

[0033] Figure 1 This is a focused ion beam (FIB) image of a cross-section of a silver-copper alloy material with a nanotwin structure deposited on a polycrystalline copper substrate in Embodiment 1 of the present invention. As can be seen from the image, the material is composed of dense columnar crystals with an average size of less than 100 nm, and has a high density of nanotwins distributed inside.

[0034] Comparative Example 1: The comparison includes the following steps: S1. Use anhydrous ethanol to ultrasonically clean the mechanically polished polycrystalline copper substrate (Ra≤0.04 μm) for 5~10 min; then dry the surface moisture with a spin dryer and set aside for later use.

[0035] S2. Place the polished and cleaned polycrystalline copper substrate and the 99.999% silver target into the magnetron sputtering stage, and adjust the distance between the substrate and the target to 20 cm.

[0036] S3. After vacuuming, the sputtering deposition process parameters are set as follows: silver target power 150 W, substrate temperature: 25℃, argon flow rate 50 sccm, argon pressure 9 mTorr, sputtering chamber vacuum degree before sputtering: 1×10⁻⁶ 5 Pa, followed by DC magnetron co-sputtering deposition on the substrate.

[0037] S4. Keep the step for 90 minutes to obtain a high-density nanotwinned silver-copper alloy material with a thickness of about 3 μm.

[0038] Figure 2 The image shows a focused ion beam (FIB) image of the cross-section of the nanotwinned silver material deposited on a polycrystalline copper substrate (single-target sputtering) in Comparative Example 1. The microstructure shows that under single-target sputtering conditions, the microstructure changes significantly. The material is composed of submicron-sized columnar crystals, with nanotwins distributed only in some of the columnar crystals. The microstructure is not uniform and there is no strong (111) preferred orientation.

[0039] Example 2:

[0040] S1. Use anhydrous ethanol to ultrasonically clean the mechanically polished polycrystalline copper substrate (Ra≤0.04 μm) for 5~10 min; then dry the surface moisture with a spin dryer and set aside for later use.

[0041] S2. Place the polished and cleaned polycrystalline copper substrate, 99.999% silver target, and 99.9995% copper target into the magnetron sputtering stage, and adjust the distance between the substrate and the target to 20 cm.

[0042] S3. After vacuuming, set the sputtering deposition process parameters as follows: silver target power 150 W, copper target power 10 W, incident angle adjusted to 0°, substrate temperature: 25℃, argon flow rate 30 sccm, argon pressure 6 mTorr, sputtering chamber vacuum degree before sputtering: 1×10⁻⁶ 5 Pa, followed by DC magnetron co-sputtering deposition on the substrate.

[0043] S4. Keep step S3 for 90 min to obtain a high-density nanotwinned silver-copper alloy material with a thickness of about 4 μm.

[0044] Figure 3 This is a FIB image of a silver-copper alloy material with a nanotwin structure deposited on a polycrystalline copper substrate in Example 2. The image shows that a silver-copper alloy material with a high-density nanotwin structure was obtained under these conditions.

[0045] Example 3:

[0046] S1. Use anhydrous ethanol to ultrasonically clean the mechanically polished polycrystalline copper substrate (Ra≤0.04 μm) for 5~10 min; then dry the surface moisture with a spin dryer and set aside for later use.

[0047] S2. Place the polished and cleaned polycrystalline copper substrate, 99.999% silver target, and 99.9995% copper target into the magnetron sputtering stage, and adjust the distance between the substrate and the target to 20 cm.

[0048] S3. After vacuuming, set the sputtering deposition process parameters as follows: silver target power 200 W, copper target power 20 W, incident angle adjusted to 0°, substrate temperature: 25℃, argon flow rate 30 sccm, argon pressure 6 mTorr, sputtering chamber vacuum degree before sputtering: 1×10⁻⁶ 5 Pa, followed by DC magnetron co-sputtering deposition on the substrate.

[0049] S4. Hold step S3 for 90 min to obtain a silver-copper alloy material with a thickness of about 4 μm and high-density nanotwins.

[0050] Figure 4 This is a FIB image of a silver-copper alloy material with a nanotwin structure deposited on a polycrystalline copper substrate in Example 3 of this invention. The image shows that a silver-copper alloy material with a high-density nanotwin structure can also be obtained under these conditions.

[0051] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions or substitutions can be made without departing from the concept of the present invention, and all such modifications and substitutions should be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a nanotwinned silver-copper alloy material, characterized in that, Includes the following steps: S1. Polish the substrate surface to Ra≤0.04 μm; S2. Perform ultrasonic cleaning and drying on the substrate; S3. Silver and copper targets were selected. The substrate and target were placed in the magnetron sputtering equipment. After evacuation, argon gas was introduced into the vacuum chamber, and a DC high-voltage electric field was applied for DC magnetron co-sputtering deposition. The incident angle was 0°, the substrate and target were spaced apart, the substrate temperature was 25 ℃, the argon gas flow rate was 30~50 sccm, the argon gas pressure was 6~9 mTorr, and the vacuum degree of the sputtering chamber before sputtering was <1×10⁻⁶. 5 Pa, deposition time is 60~90 min.

2. The method for preparing the nanotwinned silver-copper alloy material according to claim 1, characterized in that, The substrate is a copper substrate or a silicon substrate.

3. The method for preparing the nanotwinned silver-copper alloy material according to claim 1, characterized in that, The thickness of the substrate is 500~1000 μm.

4. The method for preparing the nanotwinned silver-copper alloy material according to claim 1, characterized in that, Step S2 specifically includes: ultrasonically cleaning the polished substrate with anhydrous ethanol for 5-10 minutes, shaking off the surface moisture, and then drying it.

5. The method for preparing the nanotwinned silver-copper alloy material according to claim 1, characterized in that, The purity of the silver target is 99.999%, and the purity of the copper target is 99.9995%.

6. The method for preparing the nanotwinned silver-copper alloy material according to claim 1, characterized in that, The high-voltage electric field power applied to the silver target is 100~200 W, and the high-voltage electric field power applied to the copper target is 10~30 W.

7. The method for preparing the nanotwinned silver-copper alloy material according to claim 1, characterized in that, The distance between the substrate and the target is 20 cm.

8. A nanotwinned silver-copper alloy material, characterized in that, It was prepared using the preparation method of the nanotwinned silver-copper alloy material as described in any one of claims 1 to 7.

9. The nanotwinned silver-copper alloy material according to claim 8, characterized in that, It is composed of dense columnar nanocrystals grown along the normal of the substrate with a width of less than 100 nm. The columnar nanocrystals contain a high-density nanotwin layer distributed perpendicular to the normal of the substrate. The average spacing between the nanotwin layers is less than 40 nm, and the average thickness of the nanotwin layers is 5~40 nm.

10. The nanotwinned silver-copper alloy material according to claim 9, characterized in that, The thickness of the silver-copper alloy material in the nanotwin layer is 2~10 μm.